THE EVALUATION OF DIVERSITY OF EDUCATIONAL ENVIRONMENTAL MODELS OF LATVIAN RURAL SCHOOLS - Katane, Irēna; Laizāne, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Under conditions of changes and instability in any state rural schools are faced to look for different directions of development in order to manage in the rural areas. Thus the inner structure of rural schools becomes complex and causes formation of new educational environmental models of Latvian rural schools. The aims of the article: 1) to give substantiation of the concept model; 2) to give classification of educational environmental models of rural schools; 3) to emphasize the advantages of cross-school mentoring seminars; 4) to define the most suitable and least suitable environmental model of Latvian rural schools for sustainability in the future perspective on grounds of the results of five cross-school mentoring seminars that were held in 2011.